Crossability of Triticum urartu and Triticum monococcum Wheats, Homoeologous Recombination, and Description of a Panel of Interspecific Introgression Lines. Issue 10 (1st October 2014) - Fricano, Agostino; Brandolini, Andrea; Rossini, Laura; Sourdille, Pierre; Wunder, Joerg; Effgen, Sigi; Hidalgo, Alyssa; Erba, Daniela; Piffanelli, Pietro; Salamini, Francesco
Abstract: Triticum monococcum (genome A m ) and T. urartu (genome A u ) are diploid wheats, with the first having been domesticated in the Neolithic Era and the second being a wild species. In a germplasm collection, rare wild T. urartu lines with the presence of T. monococcum alleles were found. This stimulated our interest to develop interspecific introgression lines of T. urartu in T. monococcum, a breeding tool currently implemented in several crop species. Moreover, the experiments reported were designed to reveal the existence in nature of A m /A u intermediate forms and to clarify whether the two species are at least marginally sexually compatible. From hand-made interspecific crosses, almost-sterile F1 plants were obtained when the seed-bearing parent was T. monococcum . A high degree of fertility was, however, evident in some advanced generations, particularly when T. urartu donors were molecularly more related to T. monococcum . Analysis of the marker populations demonstrated chromosome pairing and recombination in F1 hybrid plants. Forty-six introgression lines were developed using a line of T. monococcum with several positive agronomic traits as a recurrent parent. Microsatellite markers were tested on A u and A m genomes, ordered in a T. monococcum molecular map, and used to characterize the exotic DNA fragments present in each introgression line. In a test based on 28 interspecific introgression lines, the existence of genetic variation associated with T. urartu chromosome fragments was proven for the seed content of carotenoids, lutein, β-cryptoxanthin, and zinc. The molecular state of available introgression lines is summarized.